Current-mode MISO filter using CCCDTAs and grounded capacitors - Chaichana, Amornchai; Jantakun, Adirek; Kumngern, Montree; Jaikla, Winai (My University, 2015)
This paper presents the current-mode multi-input single-output (MISO) biquadratic filter using current-controlled current differencing tranconductance amplifier (CCCDTA) as an active building block. The proposed circuit comprises three CCCDTAs and two grounded capacitors performing completely standard functions: low-pass, high-pass, band-pass, bandreject and all-pass functions and does not require double input current signals as well as inverting input currents. The pole frequency and quality factor of the proposed circuit can be adjusted electronically/independently via dc bias currents. In addition, the filter circuit has low-input and high-output impedance which facilitates easy connecting for current-mode circuit. The proposed circuit uses all grounded capacitors which is very suitable to further develop into an integrated circuit and without requiring any matching condition. Moreover, the active and passive sensitivities are low. The PSPICE simulation results are included to show the workability of the proposed circuit.
Keywords: CCCDTA; Current-mode; Grounded capacitor; MISO filter